Possible Selves in Emerging Adulthood: A Comparison of Two Group Interventions - Giannone, Zarina A.; Cox, Daniel W.; Kealy, David (Canadian Journal of Counselling and Psychotherapy, 2021)
The present study provides a pilot examination of two types of possible selves group interventions. The study evaluates emerging adults’ satisfaction with and outcome following participation in groups that were oriented on interpersonal-experiential and didactic-task interventions and that focused on possible selves. Analyses used data from 85 emerging adults who were randomly assigned to one of these intervention types and who completed pre- and post-intervention assessments. Overall, participants indicated a high level of satisfaction with both types of group intervention. Results indicate that significant improvement in personal growth initiative was achieved across both interventions, but only the interpersonal-experiential intervention was associated with an increase in participants’ efficacy to pursue relational possible selves. Change in hope across both interventions was not statistically significant, and participants did not improve in their efficacy to pursue vocational possible selves. Follow-up analysis found that group engagement was associated with improvement in participants’ efficacy to pursue relational possible selves through interpersonal-experiential intervention. While both interventions appear to be beneficial, interpersonal-experiential groups may be particularly useful in fostering emerging adults’ sense of future relational selves.